1983
DOI: 10.1159/000194541
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Treatment of Pneumothorax with Oxygen Inhalation

Abstract: The treatment for pneumothorax varies from invasive chest tube drainage to conservative management with bed rest. Based on the behavior of gases in closed body cavities, the inhalation of supplemental oxygen hastens absorption of the pneumothorax. To evaluate oxygen as a therapeutic agent, we treated 8 patients with pneumothoraces of various degrees with a high concentration of inspired oxygen delivered by a partial rebreathing mask. Periodic roentgenograms were used to measure the change in size of pneumothor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 12 publications
1
40
0
1
Order By: Relevance
“…The authors suggested the faster resolution rate in the early period of oxygen therapy and the higher transpulmonary pressures in large pneumothoraces as potential mechanisms for the relation between initial pneumothorax size and resolution rate (15). Chadha et al suggested the resolution rate during oxygen supply was decreased after first 72 hours because less surface area is available for resolution (5). Our study also showed a negative correlation between the resolution rate and the time interval between radiographs.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The authors suggested the faster resolution rate in the early period of oxygen therapy and the higher transpulmonary pressures in large pneumothoraces as potential mechanisms for the relation between initial pneumothorax size and resolution rate (15). Chadha et al suggested the resolution rate during oxygen supply was decreased after first 72 hours because less surface area is available for resolution (5). Our study also showed a negative correlation between the resolution rate and the time interval between radiographs.…”
Section: Discussionsupporting
confidence: 66%
“…The effects of oxygen therapy on pneumothorax have been demonstrated on theoretical grounds and in experimental studies (3,4). In two clinical studies, the resolution rate increased by three or four times during periods of oxygen therapy (5,6). However, these two studies were based on small populations with secondary pneumothorax.…”
Section: Introductionmentioning
confidence: 99%
“…Usually pneumothoraces less than 30% of the hemithorax have a successful outcome with supplemental oxygen administration compared to those with larger than 30% who ultimately require intercostal tube drainage. 13 All the patients in the present case series had a pneumothorax less than 30% of the pleural cavity and had a positive outcome with supplemental oxygen administration. In the experimental studies on rabbit model, there was a clear advantage demonstrated in the oxygen treated group with fraction of inspired oxygen (FiO 2 ) of 0.6 compared to the controls, in terms of the rate of resolution of the pneumothorax.…”
Section: Discussionmentioning
confidence: 56%
“…Oftentimes, high concentrations of inspired oxygen can lead to a resolution of a pneumothorax that comprises less than 30% lung volume. (38) This conservative treatment of pneumothorax can reduce morbidity and duration of hospitalization and avoid invasive drainage procedures. The traditional treatment of patients with traumatic hemo-or pneumo-thoraces has been an insertion of a chest tube (CT).…”
Section: Pneumothoraxmentioning
confidence: 99%